The Effectivity of Social Workers Role at Children Resort Social Institution - Rusmiyati, Chatarina; Ikawati, Ikawati (Jurnal Penelitian Kesejahteraan Sosial, 2018)
The research on th effectivity of social workers role at Satria Baturaden Children Resort Social Institution (PSPA), is an evaluation research on the role of social workers at the social institution. The research is to reveal the effectivity of social workers role seen from the understanding of children care princip, the supporting factor of child problem handling, the implementation of child problem handling, and the success of child handling. Research location ditermined purposively underconsideration that the institution is the only technical unit in the Ministry of Social Affairs giving social welfare services to children with social problem and need special protection. Research subjects are 35 people, consisting 21 social workers, 10 benefit receivers, 9 benefit receivers parent, and 5 public figures. Data were gathered through interview, observation, documentary analysis, and FGD. Data were analyzed quatitatively. The result showed that the role of social wokers at the Satria Baturaden Social Institution was effective. The effectivity known through the effectivity of child service subsidy degree, 9,96 percent. The handicap factor of the child care implementation was the social workers lack understanding on children care and their prevention effort, lack of social work background and condition on social work science, and lack of its human recources quality and quantity. The handicap in its initial service was in identification, socialization of program subjects, selection and appropriateness of benefit receivers, assesment was yet optimum, children case data were not yet well documented, family were not participated in their children problem solving so the aftercare was not adequate, including the participation of invironment community and related institution. Based on the research result it is recommended that the Minitry of Social Affairs, through The Directorate of Child Social Welfare to set a of model concept service based on non-institution as social welfare development model through family outreach, community, and related network. The model is children problem handling based on family empowerment, community, and related network.